Analysis on Heterostructure Band Diagram Designs and Electrical Characteristics of Light Emitting Diode (LED) - Lin, Khin Ohmar; Aye, Maung; Hla, Tin Tin (The Indonesian Journal of Computer Science, 2024)
This paper presents the analysis on hetero-structure band diagram designs and electrical characteristics of light emitting diode (LED). This work is based on physical parameters of ZnCdSe, a ternary alloy semiconductor composed of Zinc (Zn), Cadmium (Cd), and Selenium (Se). In this work, the band diagram design results for n-ZnCdSe/p-Si heterojunction leds are approved by the parameters of the material such as such as effective masses of the materials, doing concentrations, electron and hole hall mobilities, bandgap bowing and so on. The electrical characteristics (energy dispersion with wave vector, intrinsic carrier concentration with temperature, intensity with wavelengths) of LED based on ZnCdSe material are also analyzed in this paper. This simulation curves are done by computer simulation. The band layer design for n-ZnCdSe/p-Si LED confirmed the high quality LED for real applications. This research gives information for the researchers who study in electronic and optoelectronic semiconductor devices.